Qiang-Xin 1 Formula Prevents Sepsis-Induced Apoptosis in Murine Cardiomyocytes by Suppressing Endoplasmic Reticulum- and Mitochondria-Associated Pathways - Xu, Xiaolong; Liu, Qingquan; He, Shasha; Zhao, Jingxia; Wang, Ning; Han, Xuyang; Guo, Yuhong (Frontiers in Pharmacology, 2018)
Sepsis is reported to be an unusual systemic reaction to infection, accompanied by multiple-organ failure. Sepsis-induced cardiomyopathy, defined as damages and dysfunction of the heart, is essential in the pathogenesis of sepsis. Traditional Chinese formula, which has long been used to improve the situation of patients through multitarget regulation, is now gradually being used as complementary therapy. The present study aimed to investigate the effect of Qiang-Xin 1 (QX1) formula, a traditional Chinese herbal medicine designed for cardiac dysfunction, on cecal ligation puncture (CLP)-induced heart damage and its underlying mechanisms in mice. Survival test first showed that an oral administration of QX1 formula significantly increased the 7-day survival of septic mice from 22% to 40%. By estimating the secretion of serum cytokines, QX1 treatment dramatically inhibited the excessive production of interleukin-1β and tumor necrosis factor-α. Immunohistochemical staining illustrated that the expression of c-Jun N-terminal kinase, caspase-12, and high-mobility group box 1 was downregulated in cardiomyocytes of the QX1-treated group compared with that of the CLP surgery group. Western blotting confirmed that the activation of essential caspase family members, such as caspase-3, caspase-9, and caspase-12, was prohibited by treatment with QX1. Moreover, the abnormal expression of key regulators of endoplasmic reticulum and mitochondria-associated apoptosis in cardiomyocytes of septic mice, including CHOP, GRP78, Cyt-c, Bcl-2, Bcl-XL, and Bax, was effectively reversed by treatment with QX1 formula. This study provided a new insight into the role of QX1 formula in heart damage and potential complementary therapeutic effect of traditional Chinese medicine on sepsis.